A quality improvement project to improve human milk feeding rate in hospitalized neonates - Sudatip Kositamongkol; Tongta Nanthakomon; Sonthaya Nukaw (Hygeia Press di Corridori Marinella, 2018)
Background: Human milk feeding is a well-established key of success to improve both short- and long-term outcomes in neonates. However, human milk feeding in hospitalized neonates faces many challenges, including limited availability of lactation specialists and bedside nurses, separation issue, mothers' and infants' illness. Our hospital has set up this quality improvement (QI) project based on Spatz's ten steps of breastfeeding in vulnerable infants since 2014. This is a report of our QI project outcome on breast milk feeding. Materials and methods: This program was launched in August 2014. The QI measures to evaluate the process were the percentage of mothers starting milk expression within 4 hours and the percentage of mothers expressing milk more than 8 times/day. The outcome measure was the proportion of neonates receiving more than 50% of mother's milk feeding during hospital stay. This project was divided into 3 phases: baseline phase, early introduction phase and sustained phase. Results: There were 563, 643 and 614 neonates admitted during baseline phase, early phase and sustained phase, respectively. Percentage of infants which received mainly mother's own milk gradually improved significantly from 49.8% ± 11.5% at baseline, to 63.1% ± 6.6% in the early phase, and up to 68.8% ± 9% in the sustained phase. The percentage of mothers starting to express milk within 4 hours was 60% ± 18.7% in the early phase and 51.9% ± 14.3% in the sustained phase (p = 0.242). The percentage of mothers expressing milk at least 8 times/day slightly increased from 52.5% ± 15.4% in the early phase to 61.9% ± 12.2% in the sustained phase (p = 0.146). Conclusions: Implementation of QI project based on Spatz's ten steps of breastfeeding in vulnerable infants has significantly improved the rate of breast milk feeding in hospitalized neonates even in a low resource setting.